Challenges, Opportunities, and Strategies of Audit Engagement in the Time of Crisis - Apelina Teresia; Bernadia Lingar Yekti Nugraheni (Jurnal Akuntansi Bisnis, 2022)
The audit process during the Covid-19 pandemic has changed due to various government regulations regarding social restrictions.  These changes impact the audit process, especially related to audit procedures due to social and mobility restrictions. Despite various challenges, auditors must maintain the audit quality. This study aims to investigate the challenges, opportunities, and strategies of audit engagement during the Covid-19 pandemic. This study conducts interviews with auditors from Big Four and Non-Big Four to investigate the challenges, opportunities, and strategies during audit engagement related to audit evidence, auditor independence, going concern opinion, and auditor-client relationships. This study applies institutional logic to generate an understanding pertaining to challenges, opportunities, and strategies during audit engagement in a time of crisis. Auditors make various efforts to adjust to the pandemic situation by carrying out various alternative procedures. Institutional logic embedded in public accounting firms has changed due to routines, relationship systems, and artifacts that are depicted in how auditors think and work because they have to adjust to the Covid-19 pandemic